Education on family medicinal plants (TOGA) for KWT Berkah Tani 2, Ngasem Village, Karanganyar - Santhyami Santhyami; Lina Agustina; Rina Astuti; Putri Agustina; Annur Indra Kusumadani; Siti Kartika Sari (Community Empowerment, 2023)
The residents of Ngasem Village already possess knowledge about the importance of Family Medicinal Plants (TOGA). However, they are not yet familiar with the benefits and methods of processing these medicinal plants. KWT Berkah Tani 2, located in Ngasem Village, Colomadu District, Karanganyar Regency, Central Java, has a large yard that remains underutilized, presenting the potential for planting TOGA. Therefore, the objective of this community service initiative is to educate the members of KWT Berkah Tani 2 about family medicinal plants, covering everything from planting to their health benefits. The program was carried out in six stages, including pre-testing, initial socialization, TOGA planting, simple processing of traditional medicinal products, post-testing, maintenance activities, and supervision. Ten types of medicinal plants were cultivated on a 700m2 area. The TOGA education program successfully increased participants' knowledge of basic TOGA concepts by 50%. Furthermore, there was a 20% rise in the number of participants who planted TOGA in their yards, and a 61.5% increase in knowledge regarding the health benefits of TOGA.